2015
DOI: 10.1016/j.jcrs.2014.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in straylight and densitometry values after corneal collagen crosslinking

Abstract: Crosslinking-induced stromal changes resulted in an increase in densitometry, especially in the anterior stroma of the central (0.0 to 2.0 mm) zone. These changes correlated with an increase in retinal straylight but not with the postoperative CDVA values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
24
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 23 publications
8
24
2
2
Order By: Relevance
“…Several studies analyzed the corneal densitometry measures following standard CXL in adult keratoconus patients. In agreement with our study, Greenstein et al [ 1 ], Alnawaiseh et al [ 31 ], Gutiérrez et al [ 32 ], and Pircher et al [ 7 ] reported a peak of corneal densitometry in the first months after standard CXL that returned to preoperative values approximately 1 year after CXL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies analyzed the corneal densitometry measures following standard CXL in adult keratoconus patients. In agreement with our study, Greenstein et al [ 1 ], Alnawaiseh et al [ 31 ], Gutiérrez et al [ 32 ], and Pircher et al [ 7 ] reported a peak of corneal densitometry in the first months after standard CXL that returned to preoperative values approximately 1 year after CXL.…”
Section: Discussionsupporting
confidence: 93%
“…Secondary to backward light scattering, the developed corneal haze following CXL can be detected clinically and graded subjectively on slit-lamp biomicroscopy and evaluated quantitatively using Scheimpflug densitometry [ 7 ]. The increased collagen fiber diameter [ 8 ], keratocyte apoptosis, and subsequent transformation into myofibroblasts [ 9 ] are the reported corneal changes on transmission electron microscopy that interpret the reduction in corneal transparency noted post-CXL.…”
Section: Introductionmentioning
confidence: 99%
“…26 The anterior layer in 0-2 mm zone has the highest densitometry level after the treatment because it received maximum treatment. 27 In addition, the age of the participants could have an impact in corneal clarity changes. 20,28 However, despite the common belief that CXL is a safe technique in children the positive effect of the treatment does not last as long in comparison to adults.…”
Section: Discussionmentioning
confidence: 99%
“…25 This is the first study of corneal densitometry in patients undergoing refractive surgery with either PRK, LASIK-FS, or ReLEx SMILE, using the latest Oculus Pentacam system software. Corneal densitometry can be used as an objective measure of corneal response after refractive surgery, and is valid for monitoring patients over time.…”
Section: Discussionmentioning
confidence: 99%